Efektivitas Inseminasi Buatan dalam Meningkatkan Produksi Sapi Perah di Indonesia - Revi Mita Lailatul Fadilah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Dairy cattle farming is a cattle breeding business specifically developed to produce large quantities of milk. Dairy cattle generally belong to the Bos taurus species, and one of the most common and productive dairy cattle breeds in Indonesia is the Holstein Friesian (FH). This study aims to evaluate how artificial insemination (AI) impacts the quantity and quality of milk produced by dairy cattle in the region, thereby contributing to improved agricultural practices and economic outcomes for dairy farmers in Indonesia. This study used a quantitative approach with a descriptive and experimental design to evaluate the effectiveness of artificial insemination (AI) on milk production in dairy cattle in Indonesia, focusing on factors influencing AI success. The results of this study indicate that artificial insemination (AI) has been proven effective in improving genetic quality and milk production in dairy cattle in Indonesia. Timely implementation of AI, especially at the peak of the estrus cycle, can increase conception rates by between 30% and 70%, with an ideal target of 65-75%. An AI program supported by inseminator training, maintained frozen semen quality, and good feed and livestock health management has a positive impact on the ideal calving interval of approximately 12 months, thereby increasing calf numbers and milk production. Artificial insemination is an effective reproductive method for increasing dairy cattle productivity through genetic improvement and controlled reproductive management. The success of an AI program depends heavily on semen quality, proper insemination techniques, livestock health management, and farmer involvement.